New Therapeutic Approaches to and Mechanisms of Ginsenoside Rg1 against Neurological Diseases - Yang Sun; Yantao Yang; Shasha Liu; Songwei Yang; Chen Chen; Meiyu Lin; Qi Zeng; Junpeng Long; Jiao Yao; Fan Yi; Lei Meng; Qidi Ai; et al. (Cells, 2022)
Neurological diseases, including Parkinson’s disease (PD), Alzheimer’s disease (AD), Huntington’s disease (HD), stroke, cerebral infarction, ischemia-reperfusion injury, depression and, stress, have high incidence and morbidity and often lead to disability. However, there is no particularly effective medication against them. Therefore, finding drugs with a suitable efficacy, low toxicity and manageable effects to improve the quality of life of patients is an urgent problem. Ginsenoside Rg1 (Rg1) is the main active component of ginseng and has a variety of pharmacological effects. In this review, we focused on the therapeutic potential of Rg1 for improving neurological diseases. We introduce the mechanisms of Ginsenoside Rg1 in neurological diseases, including apoptosis, neuroinflammation, the microRNA (miRNA) family, the mitogen-activated protein kinase (MAPK) family, oxidative stress, nuclear factor-κB (NF-κB), and learning and memory of Rg1 in neurological diseases. In addition, Rg1 can also improve neurological diseases through the interaction of different signal pathways. The purpose of this review is to explore more in-depth ideas for the clinical treatment of neurological diseases (including PD, AD, HD, stroke, cerebral infarction, ischemia–reperfusion injury, depression, and stress). Therefore, Rg1 is expected to become a new therapeutic method for the clinical treatment of neurological diseases.